Effects of tesamorelin on non-alcoholic fatty liver disease in HIV: a randomised, double-blind, multicentre trial. Issue 12 (December 2019) - Stanley, Takara L; Fourman, Lindsay T; Feldpausch, Meghan N; Purdy, Julia; Zheng, Isabel; Pan, Chelsea S; Aepfelbacher, Julia; Buckless, Colleen; Tsao, Andrew; Kellogg, Anela; Branch, Karen; Lee, Hang; et al.
Summary: Background: Non-alcoholic fatty liver disease (NAFLD) is a substantial cause of comorbidity in people with HIV and there are no proven pharmacological treatments for the disease in this population. We assessed the effects of tesamorelin on liver fat and histology in people with HIV and NAFLD. Methods: This randomised, double-blind, multicentre study with identical placebo as a comparator was done in a hospital and a medical research centre in the USA. People with HIV infection and a hepatic fat fraction (HFF) of 5% or more by proton magnetic resonance spectroscopy were eligible. Participants were randomly assigned (1:1) to receive either tesamorelin 2 mg once daily or placebo once daily for 12 months, followed by a 6-month open-label phase during which all participants received tesamorelin 2 mg daily. The randomisation list was prepared by the study statistician using a permuted block algorithm within each stratum with randomly varying block sizes. The primary endpoint was change in HFF between baseline and 12 months. The primary safety endpoint was glucose. Analysis was by intention to treat using all available data. This trial is registered with ClinicalTrials.gov, number NCT02196831 . Findings: 61 patients were enrolled between Aug 20, 2015, and Jan 16, 2019, of whom 30 received tesamorelin and 30 received placebo. Patients receiving tesamorelin had a greater reduction of HFF than did patients receiving placebo, with an absolute effect size of −4·1% (95% CI −7·6 to −0·7, p=0·018), corresponding to a −37% (95% CI −67 to −7, p=0·016) relative reduction from baseline. After 12 months, 35% of individuals receiving tesamorelin and 4% receiving placebo had a HFF of less than 5% (p=0·0069). Changes in fasting glucose and glycated haemoglobin were not different between groups at 12 months. Individuals in the tesamorelin group experienced more localised injection site complaints than those in the placebo group, though none were judged to be serious. Interpretation: Tesamorelin might be beneficial in people with HIV and NAFLD. Further studies are needed to determine the long-term effects of tesamorelin on liver histology. Funding: National Institutes of Health and National Institute of Allergy and Infectious Diseases.